Використання інформаційних технологій для мультимедійного подання інформації - Маслов, О. О.; Бутенко, О. Т.; Свідерська, Л. І. (ХНУРЕ, 2019)
To develop a textbook for distance learning, new technologies were analyzed in the field of creating interactive systems. It was found that to create a workshop in the form of a computer simulator, the most attractive are multimedia systems, which are a combination of text, sound, animation and video.